Microbial Mg-rich Carbonates in an Extreme Alkaline Lake (Las Eras, Central Spain) - Sanz-Montero, M. Esther; Cabestrero, Óscar; Sánchez-Román, Mónica (Frontiers in Microbiology, 2019)
This paper provides strong evidence for the contribution of the phylum Firmicutes in mediating the primary precipitation of Mg-rich carbonates (hydromagnesite, dolomite, magnesite, and nesquehonite) in recent microbialites from a highly alkaline and ephemeral inland lake (Las Eras, Central Spain). The carbonate mineral precipitation occurs sequentially as the microbial mats decay. Scanning electron microscopy (SEM) provided solid proof that hydromagnesite nucleation is initiated on the exopolymeric substances (EPS) and the microbial cells associated to the microbial mat degradation areas. The progressive mineralization of the EPS and bacterial cells by hydromagnesite plate-like crystals on their surface, results in the entombment of the bacteria and formation of radiating aggregates of hydromagnesite crystals. The hydrous phases, mostly hydromagnesite, were produced at a high percentage in the first stages of the microbial degradation of organic matter. When the availability of organic substrates declines, the heterotrophs tend to reduce their number and metabolic activity, remain dormant. At this stage, the anhydrous phases, dolomite and magnesite, nucleate on bacterial nanoglobules and/or collapsed cells. Evidence for the sequential formation of the Mg-rich carbonates trough the decay of organic matter by a fermentative EPS-forming bacterium isolated from the microbialites, Desemzia incerta, is drawn through a comparative analysis of carbonate formation in both natural and experimental settings. This study will help to constrain potential mechanisms of carbonate formation in natural systems, which are of fundamental importance not only for understanding modern environments but also as a window into the geologic past of Earth and potentially Mars.